Transformasi Limbah Kulit Nanas menjadi Tepache: Pelatihan Produksi Minuman Probiotik untuk Kesehatan dan Peningkatan Ekonomi Masyarakat - Sara Gustia Wibowo; Zidni Ilman Navia; Adi Bejo Suwardi; Fitriani Fitriani; Ratna Lestari; Beni Al Fajar; Rahmawati Rahmawati; Siti Faizah; Albian Mubarak; Mulia Safrida Sari (Al-Khidmah Jurnal Pengabdian Masyarakat, 2026)
Public awareness of healthy lifestyles and the benefits of natural products, including fermented beverages, has been increasing. However, fermented beverages remain relatively unfamiliar to the community, while the utilization of natural waste materials for functional products has become a major concern. One potential waste material in Telaga Meuku II Village is pineapple peel, which can be processed into a diversified functional food product known as tepache, a probiotic-rich fermented beverage with health benefits. This Community Service Program (PKM) was conducted in partnership with PKK team and residents of Telaga Meuku II Village. The partners faced several challenges, including limited education regarding the benefits of fermented beverages, inadequate skills in the fermentation process, and insufficient understanding of tepache production, packaging, and marketing.This PKM aimed to address these challenges through a series of activities carried out over four months using a participatory approach. The program stages included preparation and coordination with partners, socialization and education on probiotic beverages, hands-on training in tepache production, operational assistance, packaging guidance, as well as program monitoring and evaluation. Evaluation results based on survey analysis indicated a very good level of partner/participant satisfaction, with an average score of 3.69. In addition to increasing community awareness of the benefits of probiotic beverages, this program also created business opportunities that have the potential to improve the local community’s economy.